Boron‐Doped Diamond as an Efficient Back Contact to Thermally Grown TiO2 Photoelectrodes. Issue 17 (30th August 2019) - Ozkan, Selda; Ghanem, Hanadi; Mohajernia, Shiva; Hejazi, Seyedsina; Fromm, Timo; Borchardt, Rudolf; Rosiwal, Stefan; Schmuki, Patrik
Abstract: In the present work, we investigate the efficiency of TiO2 photoelectrode layers on boron‐doped diamond foil (BDDF) in comparison with a classic conducting glass (fluorine‐doped tin oxide, FTO) back contact. Crystalline thin TiO2 layers were prepared on the substrates by two different methods: (i) deposition of metallic Ti thin films followed by thermal oxidation to form TiO2 (TO‐TiO2 ), (ii) reactive sputter deposition of TiO2 thin films and crystallization of these layers (SP‐TiO2 ). The optimized layers show that TO‐TiO2 films on BDDF deliver a significantly higher incident photon to current efficiency (IPCE) compared to directly sputtered SP‐TiO2 layers and these layers on BDDF also outperform FTO as a back contact. We ascribe this beneficial effect of the BDDF back contact to the formation of an intermediate conductive phase of Ti carbides at the TO‐TiO2 /BDDF interface. Abstract : Back diamond : Boron‐doped diamond (BDD) acts as an excellent back contact to TiO2 layers in photoelectrochemical applications due to the formation of charge transfer redirecting interface layer.